The effects of the menstrual cycle on the task performance using two kinds of tasks - IZUMI, Hiroyuki; NINOMIJA, Satoki P.; KARASHIMA, Mitsuhiko; SUZUKI, Satoshi; KASAMATSU, Keiko; KUMASHIRO, Masaharu (Ningen kogaku. The Japanese journal of ergonomics, 2004)
This paper examines the effects of the menstrual cycle, meaning premenstruation, menstruation, and follicular phase, on two kinds of experimental tasks, and symptoms associated with menstruation. The results showed that the total number of task and reaction time for simple reaction tasks tended to be influenced by the effect of the menstrual cycle phase. Moreover, task performance in the follicular phase tended to be higher than in the other two phases. However, there was no effect of the menstrual cycle phase on task performance for responses to circumstances task. Physical changes developed during menstruation and psychological changes during premenstruation. However, the results of this paper were obtained from limited data because there were seven subjects.